Review on Retrofitting - Kumar Goyal, Pradeep; Soni, Rohit; Kumar Dhaka, Ramesh (International Journal of Computer Sciences and Engineering, 2025)
Retrofitting is a technique to increase the strength of exist building including stiffness, ductility, stability. Retrofitting is one of the best options to make an existing inadequate building safe against future probable earthquake or other environment forces. Retrofitting is the process of addition of new features to older building, heritage structure, and bridge. Retrofitting aims to strengthen a structure to satisfy the requirement of the current codes for seismic design. Retrofitting Re-strengthens of existing structure to make them more resistant to seismic action, motion of ground and failure of soil or liquefaction of soil, due to earthquake or other natural calamities such as cyclones, tornados and wind with high velocity caused by thunderstorm, hailstorm, snowfall etc. Structure loose their strength day by day so retrofitting increase their life or durability.